HUMANIZATION OF EDUCATION AND HUMANITARIAN DISCIPLINES (Алматы технологиялық университетінің хабаршысы, 2021)
The article analyzes the issues of the humanization of education. The authors emphasize the role of social - humanitarian disciplines in the education system in the spiritual modernization of modern Kazakhstan society. In modern society, the value orientations of the individual are based on his rights and freedoms, so the principles of humanization are considered as the basis for the formation of a versatile personality. At present, one of the main tasks of education and upbringing is the formation of a tolerant personality capable of respecting, accepting and correctly understanding other cultures, other ways of self-expression and manifestation of human individuality.